Al-Muhassinat al-Lafdziyah fi Syi'ri " Fata Kana Dza Hilmin" fi Kitab Diwan al-Khansa' - Hamdy, Mohammad Zainal; Aziz, Wahed Abdul; al-Ansi, Abdel Salam Hammoud Ghaleb (International Conference on Islamic Studies, 2023)
a